Practices and Attitude of Dental Clinicians towards Dental Amalgam in Lahore - Aneela Qaiser, Anam Fayyaz Bashir, Ussamah Waheed Jatala, Aisha Arshad Butt, Zenab Yaasir, Amber Fareed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Amalgam was the material of choice for dental restorations due to its excellent mechanical properties, but the World Health Organization recommended that it should be phased out due to its environmental concerns. Aim: To determine the dental clinicians’ attitude to amalgam use during routine clinical practice in Lahore. Methods: Cross-sectional study was conducted among private practicing dentists in Lahore.Using convenience sampling, 100 proformas were dispersed. The questionnaire included informed consent along with demographic data such as gender and years of practice, 17 questions related to perceptionand practices, and seven questions about knowledge of dental amalgam restorations.Chi-square test was used to determine statistical significance. P value of less than 0.05 was considered significant. Results: Seventy four questionnaires were returned filled by participants.Majority of the participants, 51 (68.9%), performed no amalgam restorations, but those with 10 years or more experience still used the material at their practices. Dentists based on clinical experience were: less than 5 years=14(18.9%), 5-10 years =31(41.9%), and more than 10 years = 29(39.2%). Significant association, p=0.02, was observed between clinical experience of clinicians and the number of amalgam restorations performed weekly in their clinics. Practical implication=Health organizations often debate about amalgam safety and the environmental issues of mercury. After the devastating floods in Sindh, environmental issues are recently raised in Pakistan. Conclusion: According to this research, dental amalgam use within private dental practitioners is definitely on a decline in Lahore. Some senior dental practitioners with 10 years or more of experienceregularly used amalgam as a restorative material. MeSH words: Dental amalgam, General Practice, Dental,